Keragaman Pertumbuhan dan Produksi Beberapa Aksesi Jarak Pagar (Jatropha curcas L.) di Daerah Pesisir Pantai - Ali Ahkamulloh; Endang Murniati; Memen Surahman (Departemen Agronomi dan Hortikultura, 2013)
The aim of this research was to know the growth various accesions of physic nut in coastal area. This research was conducted from March until October 2011 at Wonokerto Kulon coastal area, Pekalongan. The evaluated accesion were derived from 14 selected parent plants originated from Central Java, South Sulawesi, West Java and West Nusa Tenggara. The accesions were selected based on provenance trials in the previous research. The seeds were germinated in the seed nursery. The seedlings were planted in to the field (8 WAP). This research was arranged in randomized complete block design. The result of this research showed that Bogor 80-11-5 and IP-2P 110-1-4 are the best accesion. Bontomaramu 1-1, Medan and Pinrang. Sukabumi, Bengkulu 3, Gunung Tambora, Lombok 59-1-2, Aceh Besar, Bima, Bone, Dompu and Luwu Utara are not good to be planted in coastal area.Keywords: accesion, physic nut, coastal area